Bio-Inspired Hydrogel–Elastomer Actuator with Bidirectional Bending and Dynamic Structural Color - Yongqing Xia; Yaru Meng; Ronghua Yu; Ziqi Teng; Jie Zhou; Shengjie Wang (Molecules, 2023)
In nature, some creatures can change their body shapes and surface colors simultaneously to respond to the external environments, which greatly inspired researchers in the development of color-tunable soft actuators. In this work, we present a facile method to prepare a smart hydrogel actuator that can bend bidirectionally and change color simultaneously, just like an octopus. The actuator is fabricated by elastomer/hydrogel bilayer and the hydrogel layer was decorated with thermoresponsive microgels as the photonic crystal blocks. Compared with the previously reported poly(N-isopropylacrylamide) hydrogel-based bilayer hydrogel actuators, which are generally limited to one-directional deformation, the elastomer/hydrogel bilayer actuator prepared in our work exhibits unique bidirectional bending behavior in accordance with the change of structural color. The bending degrees can be changed from −360° to 270° in response to solution temperatures ranging from 20 °C to 60 °C. At the same time, the surface color changes from red to green, and then to blue, covering the full visible light spectrum. The bending direction and degree of the hydrogel actuator can easily be adjusted by tuning the layer thickness ratio of the elastomer/hydrogel or the composition of the hydrogel. The color-tunable hydrogel-elastomer actuator reported in this work can achieve both programmable deformations and color-changing highly resembling the natural actuating behaviors of creatures.